Coronary CT Angiography in Emergency Department: Can We Use It? - Purwowiyoto, Sidhi Laksono (The Indonesian Heart Association, 2017)
Acute chest pain syndrome is the main cause of patients come to emergency department. Identifying those with anamneses, risk factors, physical examination, ECG and laboratory remain challenging to exclude the acute coronary syndrome, especially those with low risk probability. Early imaging examination is important for risk stratification of these groups. Utilization of coronary CT angiography quickly identifies a group of low risk patients and allows safe and expedited discharge.   Abstrak Sindroma nyeri dada akut merupakan penyebab utama pasien datang ke unit gawat darurat. Mengidentifikasi mereka dengan anamnesis, faktor risiko, pemeriksaan fisik, EKG dan laboratorium tetap menantang untuk dapat menyingkirkan sindroma koroner akut, terutama yang dengan probabilitas risiko rendah. Pemeriksaan pencitraan awal penting untuk stratifikasi risiko kelompok ini. Penggunaan angiografi CT koroner dengan cepat mengidentifikasi kelompok pasien dengan risiko rendah dan memungkinkan pasien dipulangkan secara aman dan cepat.